Physical-chemical properties of meat from confined lambs with different levels of cottonseed in the diet - Pellegrini, Luiz Gustavo; Richards, Neila; Mello, Renius; Venturini, Rafael; Carvalho, Sérigo (Revista Ciência Agronômica, 2020)
The aim of this study was to evaluate the effect of different levels of cottonseed (0, 100, 200, 300 and 400 g Kg-1) on the physical and chemical parameters of the meat of finishing lambs. Forty-five uncastrated male lambs were distributed in a completely randomised design with five treatments of nine replications. The pH values were not influenced by the levels of cottonseed. The lipid and ash content showed significant differences, but were not adjusted by the linear or quadratic equations. Losses during thawing increased, as did cohesiveness, and water activity and water retention capacity decreased as the levels of cottonseed in the diet rose. Tocopherols, cooking loss, toughness and chewiness were adjusted using quadratic equations. In the instrumental colour evaluation, L*, b* and h° showed increasing linear behaviour. The inclusion of up to 400 g of cottonseed in the diet affects the physical-chemical composition and the colour of the produced meat.